2013
DOI: 10.5751/es-05891-180434
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Social Dimensions of Ecosystem Restoration in the Nordic Countries

Abstract: ABSTRACT. An international overview of the extent and type of ecological restoration can offer new perspectives for understanding, planning, and implementation. The Nordic countries, with a great range of natural conditions but historically similar social and political structures, provide an opportunity to compare restoration approaches and efforts across borders. The aim of this study was to explore variation in ecological restoration using the Nordic countries as an example. We used recent national assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…Vegetation zone classifications were adapted from Moen and Lilletun [40] and Rydin et al [41] for Norway and Sweden, respectively. Map is reprinted with permission from Hagen et al [42]. …”
Section: Methodsmentioning
confidence: 99%
“…Vegetation zone classifications were adapted from Moen and Lilletun [40] and Rydin et al [41] for Norway and Sweden, respectively. Map is reprinted with permission from Hagen et al [42]. …”
Section: Methodsmentioning
confidence: 99%
“…Ecosystem degradation is a pronounced problem in the Nordic countries, which has had significant negative effects on important ecosystem services, such as ecosystem resilience and carbon sequestration, as well as biodiversity (Hagen et al 2013). Restoration with the aim to produce ecosystem services has emphasized the ecosystem as something to use and benefit from.…”
Section: Integrating Eco-drr and Restoration Of Degraded Ecosystemsmentioning
confidence: 99%
“…The final report from the ReNo-project concluded that the network had consolidated knowledge on ecological restoration work in the Nordic region and facilitated exchange of this knowledge within and between the Nordic countries (Halldórsson et al 2013). The products from the ReNo-project have given essential inputs for this Nordic Aichiproject on restoration.…”
Section: Status Of Ecological Restoration In the Nordic Countriesmentioning
confidence: 99%